PENAMBANGAN PASIR ILEGAL PERSPEKTIF PERATURAN DAERAH PROVINSI KALIMANTAN BARAT DAN FATWA MAJELIS ULAMA INDONESIA - Prahesti, Diyah Sita; Sukardi, Sukardi; Suhardiman, Suhardiman (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
The purpose of this study is to find out: 1) the legal potential of illegal sand mining in North Singkawang District from the perspective of the Regional Regulation (Perda) of West Kalimantan Province and MUI Fatwa, and 2) the legal potential of illegal sand mining in North Singkawang District from the perspective of West Kalimantan Provincial Regulation and MUI Fatwa. Researchers used qualitative methods by field research and juridical-empirical approaches. Sources from primary data are in the form of observations and interviews in the field and primary legal materials, namely the Regional Regulation of West Kalimantan Province No. 09 of 2019 and MUI Fatwa No. 22 of 2011. Meanwhile, secondary data gain from books, journals, and previous research. Data collection techniques gather from observation, interviews, and documentation. The data that has been collected, researchers check the validity through a series of source triangulation and member-checks. Then, researchers analyze it through several stages, namely data reduction, data presentation, and conclusions. The results of the study indicate that: 1) the lack of good coordination between the government and the authorized mining services, as well as the government's unpreparedness in adjusting regulatory changes to the social application in society so that the implementation of the law has not been maximized; 2) violations committed by sand mining entrepreneurs create legal potential because the mining activities carried out are not in accordance with the rules contained in the Regional Regulation and environmentally friendly mining in the MUI fatwa. In addition, these mining activities cause natural damage that has an impact on the people living around the mining site. Monitoring and evaluation have become a priority for the government, especially in repairing and preventing damage.